The wind knows my name : a novel - Allende, Isabel (Ballantine Books, 2023)
"This powerful and moving novel from the New York Times bestselling author of A Long Petal of the Sea weaves together past and present, tracing the ripple effects of war and immigration on one child in Europe in 1938 and another in the United States in 2019. Vienna, 1938. Samuel Adler was six years old when his father disappeared during Kristallnacht--the night their family lost everything. Samuel's mother secured a spot for him on the last Kindertransport train out of Nazi-occupied Austria to the United Kingdom, which he boarded alone, carrying nothing but a change of clothes and his violin. Arizona, 2019. Eight decades later, Anita Diaz, a blind seven-year-old girl, and her mother board another train, fleeing looming danger in El Salvador and seeking refuge in the United States. However, their arrival coincides with the new family separation policy, and Anita finds herself alone at a camp in Nogales. She escapes through her trips to Azabahar, a magical world of the imagination she created with her sister back home. Anita's case is assigned to Selena Durán, a young social worker who enlists the help of a promising lawyer from one of San Francisco's top law firms. Together they discover that Anita has another family member in the United States: Leticia Cordero, who is employed at the home of now eighty-six-year-old Samuel Adler, linking these two lives. Spanning time and place, The Wind Knows My Name is both a testament to the sacrifices that parents make and a love letter to the children who survive the most unfathomable dangers--and never stop dreaming"--